Academician of the National Academy of Sciences of Ukraine Vadym Loktev (to his 80th birthday) - Brizhik, Larissa (Low Temperature Physics, 2025)
Dear Reader, You open the special issue of the Low Temperature Physics journal, dedicated to 80 years of outstanding Ukrainian physicist-theorist Vadym Loktev. Doctor of Science in Physics and Mathematics, Professor, Honored Worker in Science and Engineering of Ukraine, Laureate of two State Prizes of Ukraine, Academician of the National Academy of Sciences of Ukraine (NASU), a member of the Presidium of the NASU, Academician-Secretary of the Department of Physics and Astronomy of the NASU. Vadym Loktev was born on May 3, 1945 in Kyiv. Here, in Kyiv, he graduated the secondary school and in 1968 the Faculty of Physics of the National Taras Shevchenko University. His first scientific degree, candidate of science, he got in 1971 at Bogolyubov Institute for Theoretical Physics (BITP) of the NASU under the supervision of Olexandr Davydov and Elmar Petrov. At that time at the Institute of Physics of the NASU under the leadership...